Enhancing Water Quality, Growth Performance and Profitability of Outdoor Earthen Pond Shrimp Aquaculture Using Biofloc Technology - Iber, Benedict Terkula; Hossain, Shahadat; Mohd Nor, Mohd Nazli; Mazelan, Suhairi; Ismail, Nurul Hayati; Mohamad Jalilah; Draman, Ahmad Shuhaimi; Wahab, Wahidah; Mohd Razak, Mohd Syafiq; Hidayah Manan; Abdulrahim, Ahmad Ideris; Kamruzzan, Amyra Suryatie; et al. (Research in Ecology, 2025)
Global seafood demand has continued to rise amidst challenges to traditional aquaculture operations. Current shrimp aquaculture practice requires high water exchange and discharges toxic effluent to the environment. Biofloc technology (BFT) is self-sustaining and emphasizes nutrient cycling through microbial activity to maintain water quality. The effect of BFT on water quality and profitability of shrimp (Litopenaeus vannamei) culture was determined over a 70-day period. Ponds P1, P2, and P3 were treated with BFT and compared to a control group (P4) without BFT. Bacillus infantis cultured inoculum initiated biofloc development while molasses-maintained C:N ratio of 15:1. One-way ANOVA determined the mean differences in Temperature, pH, dissolved oxygen (DO), total dissolved solid, alkalinity, salinity, ammonia (NH3), nitrates, nitrites (NO2⁻), calcium, magnesium, as well as shrimp body weight (BW) and total length (TL) across treatments. Profitability was determined by comparing the cost of production with sales and plotting it on a bar chart. BFT shrimp exhibited significantly higher BW (13.6 g) compared to 8.1 g in the control, and maintained a higher survival rate (80–90%) by day 70. Water quality was better managed in BFT, with NH3 consistently kept below 0.5 mg/L; transient peaks of NO2⁻, more stable pH (averaging at 7.5), and better DO management, maintained above 5 mg/L. BFT provided higher profitability of Ringgit Malaysia (RM) 11,019.67 (P1) and RM 8651.83 (P2) compared to financial losses in the non-biofloc system. Although operational challenges were reported, BFT showed superior resilience, suggesting that proper technical training and farm management are crucial for its optimization.